A Linguistic-Based Development of Nahwu Textbooks through Blended Learning for Arabic Grammar Mastery - M Azizul Kiram; Kristina Imron; Rendi Sabana (Al-Irfan : Journal of Arabic Literature and Islamic Studies, 2026)
This research aims to develop a basic Nahwu Science textbook based on blended learning and measure its effectiveness in improving the understanding of grade VIII students at Prof. Muhajirin Applied Islamic Junior High School Palembang. The method used is a mix-method with the Design and Development (R&D) of the ADDIE model. Qualitative data was obtained through observation, interviews, and documentation, while quantitative data was obtained through pretest and posttest tests of 25 students. The results showed that the textbooks developed were very feasible to use (validation of material experts 89%, validation of media experts 85%) and practical according to teachers (88%) and students (82%). The average pretest score of 56.8 increased to 81.2 in the posttest, with an N-Gain value of 0.67 (moderate category close to high). This textbook effectively improves student understanding through visual, contextual, and online and offline practice support. These findings strengthen the relevance of the use of blended learning in learning Nahwu Science at the junior high school level.